Applied operational excellence for the oil, gas, and process industries - Nolan, Dennis P.; Anderson, Eric T. (Elsevier : GPP, 2015)
Applied Operational Excellence for the Oil, Gas, and Process Industries offers a straightforward practical guide for oil and gas companies to understand the comparisons and contrasts between various types of safety management processes, including the standardized structure and ongoing extended benefits that operational excellence can bring to an oil and gas company. The goal of achieving operational excellence is to reduce costs, improve productivity, and enhance efficiency--in other words, operational excellence contributes to the bottom line. Following along with pre-built success in the process industries, many companies in the oil and gas industry appear to use a subset form of operational excellence, yet many are unsure or unaware of all the safety system components that will truly benefit the company holistically, and current literature is only applicable to the process and manufacturing industries. Packed with clear objectives and tools, structure guidelines specific to oil and gas, and guidance for how to imbed your existing safety program under the operational excellence umbrella known as "One-Step Merger," this book will help you establish an overall safety culture vision and challenge your organization to achieve higher levels of safety management and overall company value. Explores how to solidify a foundational operational excellence program applicable for your oil and gas company Clarifies the differences and benefits among various programs under operational excellence (OE), such as SHE (safety, health, and environment), PSM (process safety management), and SMS (safety management system) Explains how to audit and consistently assess how oil and gas OE systems are planned, implemented, and managed, with explanations on cost and time impacts as well as administrative protocols Includes a glossary, acronym appendix, and additional references for further reading.